Emotional status of final year MBBS Students in a private medical college in central Kerala, India - Varghese, Anju; Joseph, Elizabeth; N. P., Sunil; T. M., Celine; Raj, Renjith (International Journal of Advances in Medicine, 2016)
Background: Medical education is highly stressful for students. They repeatedly experience different stressors which make them vulnerable for psychological problems.This study was undertaken to determine the prevalence of stress, anxiety and depression among the Final year MBBS students. Methods: A questionnaire based study was conducted among 157 Final year MBBS students. The DASS 42 scale described by Lovibond and Lovibond was used. DASS baseline scores were collected during relaxed state when there is no exam and in a stressful condition, one week before the sessional exam. Results: DASS questionnaire collected from 157 students showed that anxiety score was higher in tensed state while the stress and depression scores were higher in relaxed state. Stress, anxiety and depression scores of females are more than males in relaxed state. Conclusions: There is increased prevalence of depression, anxiety and stress among the medical students. The severity is more among the females. Early screening and intervention are advisable because it will help the students in reducing their stress, anxiety and depression which are in their initial phase and can be managed easily with few sessions of counselling.